Effect of internal taper of endocrown preparation on the adaptation of 3D-printed restorations - Mahdi Zerafat; Marzieh Alikhasi; Negin Yaghoobi; Nikfam Khoshkhounejad (Journal of Dental Materials and Techniques)
Objective: This study aimed to evaluate the influence of different internal taper angles in endocrown preparations on the marginal and internal adaptation of 3D-printed restorations.Methods: Three standardized mandibular first molar models were prepared with internal taper angles of 6°, 10°, and 22°. Each model was scanned 12 times, and endocrown restorations were digitally designed and fabricated with a 3D printer using Freeprint® Temp resin. All restorations were seated by a single operator, and the adjustment time and frequency were recorded. Adaptation was assessed using the replica technique, and marginal, axial, pulpal, and axio-pulpal line angle gaps were measured under a stereomicroscope. Data were analyzed using one-way ANOVA and Tukey’s post-hoc test at the significance level of P<0.05.Results: The pulpal gap was significantly larger in the 22° taper group compared to both the 6° (P<0.001) and 10° (P=0.001) groups. The 6° taper group exhibited significantly greater marginal misfit than the 10° (P=0.035) and 22° (P=0.021) groups. The axio-pulpal line angle misfit was significantly higher in the 22° taper group than in the 6° group (P=0.016). No significant difference was observed in axial misfit among the groups (P=0.169). Notably, the 22° taper group required significantly less adjustment time and fewer adjustment attempts than the other groups (P<0.05).Conclusions: All three taper angles yielded restorations with clinically acceptable adaptation. Increasing the internal taper from 6° to 22° improved marginal fit and reduced clinical chairside adjustments; however, it resulted in a deterioration of pulpal adaptation.